Chapter Functional Annotation of Rare Genetic Variants - Ritchie, Graham (Springer Nature, 2015)
Genome-wide association studies have successfully identified a growing number of common variants that robustly associate with a wide range of complex diseases and phenotypes. In the majority of cases though, the variants are predicted to have small to modest effect sizes, and, due to the technologies used, many of the signals discovered so far may not be the causal loci. As rare variation studies begin to explore the lower ranges of the allele frequency spectrum, using whole genome or whole exome sequencing to capture a larger proportion of variants, we expect to find variants with a more direct causal role in the phenotype(s) of interest. Interpreting possible functional mechanisms linking variants with phenotypes will become increasingly important.